Oracles et grande politique en Grèce ancienne : Le cas de l’orgas sacrée et de la consultation de Delphes en 352/351 avant J.-C.1 (1ère partie) - Bonnechere, Pierre (Dossier : Serments et paroles efficaces, 2017)
Thanks to a case study, this paper aims at revisiting the old problem of the political influence of Greek oracles on big politics. In the tense international context of the 3rd sacred war, Athens decides to demarcate a sacred land at Eleusis, which was then cultivated by the Megarians (IG II2, 204), and consequently to consult the pythia. The procedure of consultation, which seems excessively controlled by the ecclesia, has always been considered as a clear mark of political defiance. A close analysis of the text proves this assertion to be debatable and leads to a re-evaluation of the boundary marking and its immediate context. The second part of this paper will deal properly with the «political implications» of the oracle.,L’étude se propose de revenir sur la vieille question de l’influence des oracles sur la grande politique, grâce à un cas d’école. Dans le contexte international tendu de la 3e guerre sacrée, Athènes décide de borner un terrain sacré à Éleusis, que les Mégariens avaient mis en culture (IG, II2, 204), et prévoit de consulter la pythie. La procédure de consultation, qui semble contrôlée à l’extrême par l’ecclésia, y a toujours été interprétée de façon politique. Une analyse attentive du document permet de mettre en doute cette assertion, et rend nécessaire la reprise complète du dossier de bornage et de son contexte immédiat. La seconde partie analysera les « implications politiques » de l’oracle à proprement parler.
Keywords: 3e guerre sacrée; 3rd sacred war; Delphic oracle; Eleusis; Hymnes homériques; Ovide; Parthenos; Phryne; Phryné; Varron; abstention vow; beauty; bornage; boundaries; charis; corps; daimôn; democracy; divine witnessing; démocratie; epiphany; katadesmoi; kolossoi; langage; language; malédiction réflexive; metamorphosis; métamorphose; oath; offrande musicale; oracle de Delphes; ornement; poetics and pragmatics; poitrine; politics; politique; ritual; ritualization; rituel; sacrifice; serment; statue; témoignage divin; témoins humains; vows; vœu d’abstinence; vœux; Éleusis